EQUIVALENCE OF PROPER NAME IN FOREIGN LANGUAGE INTO THE INDONESIAN LANGUAGE - Suhardi Suhardi; Pratomo Widodo; Teguh Setiawan (LITERA, 2019)
Translation of self-names becomes important if it is associated with important documents, such as agreement documents and inter-institutional or interstate cooperation. This study aims to describe the type of self-name of a foreign language that is translated into Indonesian and describes the procedure of equivalence of self-names in foreign languages into Indonesian. The source of this qualitative research data is the Indonesian online newspaper, while the research data is all words which are the names of the translation results from English. Data collection is done by reading and writing. The instrument of this study is a human instrument based on indicators of language units in the form of self names. The analysis technique used is a translational equivalent. The results of the study are as follows. First, there are four types of self-names of foreign languages that are translated into Indonesian, namely people's names, geographical names, institution names, and celebrations. The name itself is made up of three patterns, namely a combination of general vocabulary, a combination of general vocabulary and self names, and a combination of self-names. Self-name patterns will affect the translation procedure. Second, there are four equivalent procedures for self-names in foreign languages in Indonesian, namely transfer, substitution, translation, and modification. People's names use transfer, substitution and translation procedures. Geographical names use transfer, substitution, translation and modification procedures. The name of the institution uses translation and transfer procedures. The name of the celebration or festival uses translation and transfer proceduresKey Word: equivalence, proper name, transfer, substitution, modification EKUIVALENSI NAMA DIRI DALAM BAHASA ASING KE DALAM BAHASA INDONESIA AbstrakPenerjemahan nama diri menjadi penting jika dikaitkan dengan dokumen penting, seperti dokumen penjanjian dan kerjasama antarlembaga atau antarnegara. Penelitian ini bertujuan menjabarkan tipe nama diri bahasa asing yang diterjemahkan ke dalam bahasa Indonesia dan menjabarkan  prosedur ekuivalensi nama diri dalam bahasa asing ke dalam bahasa Indonesia. Sumber data penelitian kualitatif ini adalah surat kabar on line berbahasa Indonesia, sedangkan data penelitian ini adalah semua kata yang merupakan nama diri hasil penerjemahan dari bahasa Inggris. Pengumpulan data dilakukan dengan cara baca dan tulis. Instrumen penelitian ini adalah human instrumen dengan berpedoman pada indikator satuan bahasa yang berupa nama diri. Teknik analisis yang digunakan adalah padan translasional.  Hasil penelitian sebagai berikut. Pertama, ada empat tipe nama diri bahasa asing yang diterjemahkan ke dalam bahasa Indonesia, yaitu nama orang, nama geografis, nama lembaga, dan nama perayaan. Nama diri tersebut ada yang terbetuk dari tiga pola, yaitu gabungan kosakata umum, gabungan kosakata umum dan nama diri, dan gabungan nama diri. Pola nama diri akan berpengaruh pada prosedur penerjemahannya. Kedua, prosedur ekuivalensi nama diri dalam bahasa asing  ke dalam bahasa Indonesia ada empat, yaitu transfer, substitusi, penerjemahan, modifikasi. Nama diri orang menggunakan prosedur transfer, substitusi, dan penerjemahan. Nama geografis menggunakan prosedur transfer, substitusi, penerjemahan, dan modifikasi. Nama  lembaga menggunakan prosedur penerjemahan dan transfer. Nama perayaan atau festival menggunakan prosedur penerjemahan dan transfer. Kata Kunci: ekuivalensi, nama diri, transfer, substitusi, modifikasi